1997
DOI: 10.1046/j.1365-2818.1997.2630819.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of autofocus functions in molecular cytogenetic analysis

Abstract: SummaryThis work describes a systematic evaluation of several autofocus functions used for analytical fluorescent image cytometry studies of counterstained nuclei. Focusing is the first step in the automatic fluorescence in situ hybridization analysis of cells. Thirteen functions have been evaluated using qualitative and quantitative procedures. For the last of these procedures a figure-of-merit (FOM) is defined and proposed. This new FOM takes into account five important features of the focusing function. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
277
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 346 publications
(286 citation statements)
references
References 12 publications
7
277
0
2
Order By: Relevance
“…Numerous focus measures have been presented in the literature (Krotkov, 1987;Gillespie et al, 1989;Firestone et al, 1991;Yeo et al, 1993;Santos et al, 1997;Choi et al, 1999;Subbarao and Tyan, 1998;Widjaja and Jutamulia, 1998;Geusebroek et al, 2000;Chern et al, 2001;Lin et al, 2004;Yap and Raveendran, 2004). From among these we selected four well-known measures to compare against our measure.…”
Section: Reference Measures Of Focusmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous focus measures have been presented in the literature (Krotkov, 1987;Gillespie et al, 1989;Firestone et al, 1991;Yeo et al, 1993;Santos et al, 1997;Choi et al, 1999;Subbarao and Tyan, 1998;Widjaja and Jutamulia, 1998;Geusebroek et al, 2000;Chern et al, 2001;Lin et al, 2004;Yap and Raveendran, 2004). From among these we selected four well-known measures to compare against our measure.…”
Section: Reference Measures Of Focusmentioning
confidence: 99%
“…The fourth measure, known as Vollath's F 4 , was reported by Santos et al (1997) to achieve good focusing, even in low-information-content images, and is defined as…”
Section: Reference Measures Of Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a good deal of literature on the subject of autofocus for microscopy and robotics in general (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Fitted with a video or digital camera and a motorized stage under computer control, the typical autofocus microscope system uses two complementary algorithms to achieve focus.…”
mentioning
confidence: 99%
“…For brightfield imaging, this focus function establishes a roughly parabolic relation between focus score and position. Acceptable focus functions have been described for brightfield (7), phase-contrast (8), and fluorescence (5,6,8) imaging, and a general method has been described (3); however, Groen et al (11) found that focus functions optimized for one imaging mode may not perform well in another. This may be particularly relevant to Nomarski-DIC because optical sectioning may resolve detail in multiple planes within a subject, potentially resulting in a multimodal focus function.…”
mentioning
confidence: 99%